Effects of aluminum incorporation on the schwertmannite structure and surface properties. Issue 9 (15th July 2022) - Carrero, Sergio; Fernandez-Martinez, Alejandro; Pérez-López, Rafael; Cama, Jordi; Dejoie, Catherine; Nieto, José Miguel
Abstract : Aluminum in schwertmannite structure increases the proportion of covalent bonding with adsorbed arsenates. Abstract : Schwertmannite is a common nanomineral in acid sulfate environments such as Acid Mine Drainage (AMD) and Acid Sulfate Soils (ASS). Its high surface area and positively charged surface result in a strong affinity towards toxic oxyanions such as arsenate in solution. However, natural precipitation of schwertmannite also involves the accumulation of other impurities, in particular aluminum, an element that is often incorporated into the structure of Fe-oxide minerals, such as goethite and ferrihydrite, affecting their structural and surface properties. However, little is known about the effect of Al incorporation in schwertmannite on the removal capacity of toxic oxyanions found in AMD and ASS ( e.g. arsenate). In this paper, schwertmannite samples with variable Al concentration were synthetized and employed in arsenate adsorption isotherm experiments at a constant pH of 3.5. Solid samples before and after arsenate adsorption were characterized using high energy X-ray diffraction and pair distribution function analyses in order to identify structural differences correlated with the Al content as well as variations in the coordination of arsenate adsorbed on the mineral surface. These analyses showed limited Al accumulation on schwertmannite (up to 5%) with a low effect on its structure. The maximum arsenate sorption capacity (258 mmolH2 AsO4 molFe −1 ) was in the range of that with pure schwertmannite, but a higher proportion of inner-sphere coordination was observed. Finally, Al was found to desorb from schwertmannite, with adsorbed arsenate preventing this effect and increasing the stability of the mineral. These results are useful to interpret observations from the field, in particular from river water affected by AMD and ASS, where similar conditions are observed, and where aluminum incorporation is expected.